Analisis Data Profil SMA Dalam Kolaborasi Keterampilan Mengajar Mahasiswa Geografi - Ryan Pramana; Cindy Melissa; Ivan Rivaldo; Wafiq Ariska; Ame Mahisa; Roy Eka (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
This research highlights the importance of collaboration between universities and schools in preparing student teachers to face modern educational trends through practical teaching experience in the field. The focus of the research is on the geography learning assessment process in three high schools in Medan (SMAN 1, SMAN 2, SMAN 3), including the creation of Learning Implementation Plans (RPP), evaluation, and the obstacles faced by teachers. The research method used is descriptive qualitative with observation, interviews and document analysis. The research results show that SMAN 1 Medan uses CBT-based formative and summative assessments, with some students facing health problems and a lack of gadgets. At SMAN 2 Medan, assessments integrate HOTS and digital applications such as Quizizz and Google Forms, but students experience impaired focus due to cellphone use in class. SMAN 3 Medan follows the 2013 Curriculum and Merdeka Curriculum guidelines in making lesson plans, with evaluation using digital tools and This research provides insight into the practices and challenges in assessing geography learning as well as suggestions for improving assessment methods and providing more comprehensive learning tools.